(Un)interrupted Journey: Experiences of Health Disorders in Women’s Travel Narratives - Gintalaitė, Agnė (Tautosakos darbai, 2025)
The article analyzes women’s experiences of health disturbances during travel in the context of lifestyle mobilities and migration. The study reveals how women who understand travel as an emancipatory practice of gaining freedom and autonomy encounter unexpected situations of immobilization and dependency, and what meanings the experiences of passivity and care acquire in this context. The research material consists of the author’s autoethnographic diary and four interviews with Lithuanian women travelers conducted in 2025 in Fuerteventura and remotely. The phenomenological approach makes it possible to understand that the physical standstill experienced during illness does not necessarily signify a rupture in the journey or a loss of freedom. On the contrary, passivity may become an alternative form of agency, when dependence on others and acceptance of care liberate one from the demands of constant control and productivity. Sara Ahmed’s affect theory helps to reveal how the hospital can become a space that permits what in ordinary everyday life appears to deviate from norms or is even prohibited and stigmatized. Outside the hospital, even when experiencing severe physical impairment, women still strive to maintain a controlling relation to the world, to care rather than to accept care, or to accept it only conditionally, which intensifies tension and discomfort.